Analisis nilai moral dalam cerita rakyat Saridin yang sakti di Pati - Suprapti, Suprapti; Kanzunuddin, Moh.; Fathurohman, Irfa’I (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to identify and analyze the moral values ​​contained in the folklore